Chlordiazepoxide dichloromethane monosolvate - Fischer, Andreas (International Union of Crystallography, 2012)
In the title compound (systematic name: 7-chloro-2-methylamino-5-phenyl-3H-1,4-benzodiazepine 4-oxide dichloromethane monosolvate), C(16)H(14)ClN(3)O·CH(2)Cl(2), the seven-membered ring adopts a boat conformation with the CH(2) group as the prow and the two aromatic C atoms as the stern. The dihedral angle between the benzene rings is 75.25 (6)°. The crystal structure features centrosymmetric pairs of chlordiazepoxide molecules linked by pairs of N—H⋯O hydrogen bonds, which generate R (2) (2)(12) loops.